A Type 2 Diabetes Patient who Suffered with Fournier’s Gangrene - Kholidatul Husna; Hermina Novida (Current Internal Medicine Research and Practice Surabaya Journal, 2021)
Diabetes mellitus increases the risk of infection, including Fournier’s gangrene. Fournier’s gangrene (FG) is a rare case, with an average incidence of 1.6 cases per 100,000 population per year. We report a case of a 60 year old male, presented with the history of wounds of the buttocks, penis and scrotum. The patient had a history of uncontrolled diabetes mellitus for 3 years. There were perianal abscesses and necrotic tissue on the penis and scrotum. Radiological evaluation in the patient showed the present of gas forming in scrotal area. Therefore, incision and drainage procedure with necrotomy and debridement were performed, together with antibiotics and blood glucose regulation, then followed by closure of the defect with skin graft and use of flap. The patient was discharge with an improved clinical condition.